2019
DOI: 10.1111/j.1936-704x.2019.03321.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Perceptions and Attitudes about Water Issues in Oklahoma: A Comparative Study

Abstract: Understanding people’s perceptions of the environment, drinking water issues, and protecting and preserving water resources is of great importance. This study aims to assess and compare the perceptions of the general public (n = 414), post‐secondary students (n = 103), and water professionals (n = 104) in Oklahoma on water issues in the state. To address these goals, a 53‐item paper questionnaire was first administered to a randomly sampled mailing list of Oklahoma residents. As a follow up to the initial surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Cooper and Cockerill [6] found, as compared to the public, students were less concerned about future household water supply and thought less about water conservation. Conversely, Eck et al [74] found that of 27 water issues in Oklahoma, USA, two of the most important issues identified by students, the public, and professionals alike were clean drinking water and clean rivers and lakes. However, students diverged from the other groups in assigning particularly high importance to agricultural water and land preservation and practices.…”
Section: Student Attitudes Values and Actionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooper and Cockerill [6] found, as compared to the public, students were less concerned about future household water supply and thought less about water conservation. Conversely, Eck et al [74] found that of 27 water issues in Oklahoma, USA, two of the most important issues identified by students, the public, and professionals alike were clean drinking water and clean rivers and lakes. However, students diverged from the other groups in assigning particularly high importance to agricultural water and land preservation and practices.…”
Section: Student Attitudes Values and Actionsmentioning
confidence: 99%
“…Perceptions related to drinking water quality among students is also a topic that has been surveyed with some breadth. Students often show a high trust in the safety of drinking water [70,74], though high school students may still prefer to drink bottled water [72]. Either due to or regardless of misconceptions, German undergraduates accepted the idea of using recycled water, particularly for non-consumptive uses [68].…”
Section: Student Attitudes Values and Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previous regional studies [14,30,39], Oklahoma residents considered clean drinking water, clean rivers, and clean underground water to be the highest priority water related issues in the state. A comparative study of different water stakeholders (residents, students, water professionals) also found clean water as a major issue in the state [40]. Although residents perceived all water issues to be important, we were able to cluster respondents into distinct groups based on their level of perceived importance of each water issue.…”
Section: Discussionmentioning
confidence: 84%
“…More effective delivery will be required as well. These efforts will require the use of printed materials and television (for those over 50), along with social media and informational videos (for those under 34) to reach the broader public (Eck et al, 2019).…”
Section: Discussionmentioning
confidence: 99%